2010
DOI: 10.1002/stem.466
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reprogramming Efficiency Between Transduction of Reprogramming Factors, Cell–Cell Fusion, and Cytoplast Fusion  

Abstract: Reprogramming human somatic cells into pluripotent cells opens up new possibilities for transplantation therapy, the study of disease, and drug screening. In addition to somatic cell nuclear transfer, several approaches to reprogramming human cells have been reported: transduction of defined transcription factors to generate induced pluripotent stem cell (iPSC), human embryonic stem cell (hESC)-somatic cell fusion, and hESC cytoplast-somatic cell fusion or exposure to extracts of hESC. Here, we optimized techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Alternatively, this could also be the result of the differentiation bias of the hybrid cells as observed here. Taken together, our results extend previous studies [3,[9][10][11][12][13][14][15][16][17][18][19], where somatic cells were fused with ES cells to study reprogramming and induction of pluripotency. Here we show that fusion with somatic cells impacts on the differentiation propensity of pluripotent stem cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Alternatively, this could also be the result of the differentiation bias of the hybrid cells as observed here. Taken together, our results extend previous studies [3,[9][10][11][12][13][14][15][16][17][18][19], where somatic cells were fused with ES cells to study reprogramming and induction of pluripotency. Here we show that fusion with somatic cells impacts on the differentiation propensity of pluripotent stem cells.…”
Section: Discussionsupporting
confidence: 89%
“…Cell fusion was used as an approach to study reprogramming of somatic cells toward pluripotency [3,[9][10][11][12][13][14][15][16][17][18][19][20]. Shortly after fusion, hybrid cells acquire similar characteristics as the parental pluripotent stem cells.…”
mentioning
confidence: 99%
“…In a recent study, the reprogramming time course was compared between the technology of iPSCs and somatic cells-ESCs fusion. The results showed that reprogramming human fibroblast into iPSCs required more than 4 weeks; it was slower than the cell fusion in which less than 10 days was required to reprogram human fibroblast into ESCs (Hasegawa et al 2010). While in a study of interspecies SCNT, human fibroblasts, and rabbit oocytes were used as nuclear donors and nuclear recipients, respectively, a proportion of hybrid embryos required only 5-7 days to develop to hatched blastocysts, and the inner cell mass could be used to generate ESCs .…”
Section: Matured Oocytes Were Endowed With Totipotent Developmental Pmentioning
confidence: 99%
“…In addition to somatic cell nuclear transfer, the most common reprogramming method is achieved by introduction of defined transcription factors (Oct4, Sox2, c-myc, Klf4, and nanog) into the somatic cells. However, this method is asynchronous and slow (more than 4 weeks), and the efficiency is less than 0.001% in iPSC generation (Hasegawa et al 2010). Recently, it has been demonstrated that cell fusion with human embryonic stem cells provides much faster and efficient method (less than 1 day and achieves 70% efficiency) for reprogramming somatic cells to a pluripotential state (Cowan et al 2005;Bhutani et al 2010).…”
Section: Introductionmentioning
confidence: 98%